The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.ijepes.2014.12.088
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of post-contingency congestion risk of wind power with asset dynamic ratings

Abstract: a b s t r a c tLarge scale integration of wind power can be deterred by congestion following an outage that results in constrained network capacity. Post outage congestion can be mitigated by the application of event control strategies; however they may not always benefit large wind farms. This paper investigates this problem in detail and proposes an advanced mathematical framework to model network congestion as functions of stochastic limits of network assets to capture post contingency risk of network conge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The effectiveness per line with DLR also installed strongest at the first few lines to then level out. V. CONCLUSION The results presented in the previous sections have shown that a congested distribution system can present different results with the implementation of DLR compared with previous studies [17]- [19]. Due to the limits and constraints in OPF formulation, it is observed that limits other than thermal, such as voltage limits, are present in the system and can have a considerable impact on the results obtained.…”
Section: Influence Of the Number Of Dynamically Rated Linesmentioning
confidence: 81%
“…The effectiveness per line with DLR also installed strongest at the first few lines to then level out. V. CONCLUSION The results presented in the previous sections have shown that a congested distribution system can present different results with the implementation of DLR compared with previous studies [17]- [19]. Due to the limits and constraints in OPF formulation, it is observed that limits other than thermal, such as voltage limits, are present in the system and can have a considerable impact on the results obtained.…”
Section: Influence Of the Number Of Dynamically Rated Linesmentioning
confidence: 81%
“…The contingency analysis consists of three basic steps to make it simpler. They are listed below [12]:…”
Section: Power System Contingency Analysismentioning
confidence: 99%
“…Banerjee et al [43] conducted a congestion prevention strategy during outage conditions of both N-1 and N-2 by DLR implementation in order to reduce wind power curtailment or re-dispatch. The operational cost minimization-oriented study in [43] defined a cost variable for DLR implementation as a constraint relaxation penalty apart from the other cost components regarding conventional generators based power production, wind power uncertainty and congestion. The mentioned study in [43] also considered the stochasticity of wind power production in the evaluation as a notable difference compared to many existing DLR based operational studies.…”
Section: Solely Dlr Based Operational Flexibilitymentioning
confidence: 99%
“…The operational cost minimization-oriented study in [43] defined a cost variable for DLR implementation as a constraint relaxation penalty apart from the other cost components regarding conventional generators based power production, wind power uncertainty and congestion. The mentioned study in [43] also considered the stochasticity of wind power production in the evaluation as a notable difference compared to many existing DLR based operational studies. An interesting study considering also the stochasticity of wind power as well as the load demand, component availability and weather variables (wind speed, solar radiation, ambient temperature) leading to a stochastic DLR capacity as the overall resources of uncertainty in the system operation was portrayed in [44].…”
Section: Solely Dlr Based Operational Flexibilitymentioning
confidence: 99%